SAT0039 ZAP-70 CONTROLS AUTOIMMUNE ARTHRITIS VIA REGULATION OF APOPTOSIS THROUGH BCL-2, BIM AND CBL IN T CELLS. (June 2019) - Kugyelka, Reka; Prenek, Lilla; Kohl, Zoltan; Glant, Tibor; Nemeth, Peter; Berki, Timea; Boldizsar, Ferenc
Abstract : Background: The recombinant human G1(rhG1)-induced mouse arthritis (GIA) model resembles human rheumatoid arthritis in many aspects 1 . Similarly, to RA, GIA is also a T cell dependent disease: T cell activation and apoptosis has been shown to regulate arthritis severity 2 . ZAP-70 kinase is a key molecule of T cell receptor signaling, in its absence T cell differentiation and activation is seriously hindered 3 . In preliminary experiments, we found that partial ZAP-70 deficiency (in ZAP-70 +/- heterozygous mice) ameliorated autoimmune arthritis in the GIA model, supported by both in vivo (decreased severity and milder arthritis) and in vitro tests (decreased T cell proliferation, IL-4 and IL-6 production). Objectives: In the present work we wanted to test the hypothesis that the observed changes in GIA in partial ZAP-70 deficient mice are due to complex alterations in T cell apoptosis. Methods: T cells were isolated from healthy and arthritic BALB/c and ZAP-70 heterozygous (ZAP-70 +/- ) knockout mice, then stimulated in vitro for 72 hours with anti-CD3/anti-CD28-coated beads. After stimulation, cells were lysed and the homogenates were subjected to Western-bloting using antibodies against activated Caspases-3, -8, and -9, respectively, and other apoptotic markers (cytochromeC), and some important regulator molecules (Bcl-2, Bim and Cbl). Results: Overall, as expected, we have seen decreased tyrosine phosphorylation in the T cells of arthritic ZAP-70 +/- mice compared to the controls. The levels of cleaved (activated) Caspase-8 and -9 were comparable in ZAP-70 +/- samples to the controls, however, we detected elevated levels in case of Caspase-3. There was slightly lower Cytochrome C release and Bcl-2 and Bim levels in the activated T cells of ZAP-70 +/- mice. Importantly, there was markedly less Cbl-b in the T cells of arthritic ZAP-70 +/- mice. Conclusion: Our results show the complex changes in the apoptotic pathways of activated T cells caused by the partial deficiency of ZAP-70. Impaired T cell activation through the T cell receptor complex, as shown by decreased phosphorylation, accompanied by slightly increased apoptosis sensitivity of T cells (stronger Caspase-3 signal) might explain the less severe arthritis seen in ZAP-70 +/- mice. Furthermore, based on these results Cbl-b (a negative regulator of T cell activation) might serve as an important early molecule interacting with ZAP-70 and thus fine regulate T cell activation and apoptosis in autoimmune arthritis. References: [1] Glant TT, Radacs M, Nagyeri G, Olasz K, Laszlo A, Boldizsar F, Hegyi A, Finnegan A, Mikecz K. Arthritis Rheum. 63(5):1312-21., 2011 [2] Hanyecz A, Olasz K, Tarjanyi O, Nemeth P, Mikecz K, Glant TT, Boldizsar F. Biomed Res Int. 2014:942148., 2014 [3] Kadlecek TA, van Oers NSC, Lefrancois L, Olson S, Finlay D, Chu DH, Connolly K, Killeen N, Weiss A. J Immunol. 161:4688-4694; 1998 Acknowledgement: Funding: OTKA K101493; EFOP-3.6.1.-16-2016-00004; GINOP 2.3.2-15-2016-00050; KA-2015-23 to K.O.; BO/00086/12/5 to F.B.; 716/180/2014/KIF to K.O.; KA-POSTDOK-12-05 to K.O. Disclosure of Interests: None declared